Straw coverage no -tillage fertilizing seeder - LIU JUNFENG; YUAN PENGFEI; ZHANG TIANQING; YUE ZHIGANG; YAN HUAIMIN (2017)
The utility model discloses a straw coverage no -tillage fertilizing seeder, including the frame, frame top is from precedingly install gauge wheel, transmission assembly, seeding fertilizer injection?unit after to, broadcast that the autumn clothing is put and compression roller in proper order, and rotary tillage arbor and fertilizing?and?seeding furrow opener, the epaxial rotary blade of installing of rotary blade are installed to the frame below. The utility model relates to a straw coverage no -tillage fertilizing seeder uses this machine operation, can reduce the farming by a wide margin and drop into, improves soil structure, and yield increasing effect is obvious. 本实用新型公开了种秸秆覆盖免耕施肥播种机，包括有机架，机架上方自前至后依次安装有限深轮、变速箱总成、播种施肥装置、播秋装置和镇压辊，机架下方安装有旋耕刀轴和施肥播种开沟器，旋耕刀轴上安装有旋耕刀。本实用新型是种秸秆覆盖免耕施肥播种机，使用该机作业，可大幅减少耕作投入，改善土壤结构，增产效果明显。